Genetic approaches in improving biotechnological production of taxanes: An update - Perez-Matas, Edgar; Hidalgo-Martinez, Diego; Escrich, Ainoa; Alcalde, Miguel Angel; Moyano, Elisabeth; Bonfill, Mercedes; Palazon, Javier (Frontiers in Plant Science, 2023)
Paclitaxel (PTX) and its derivatives are diterpene alkaloids widely used as chemotherapeutic agents in the treatment of various types of cancer. Due to the scarcity of PTX in nature, its production in cell cultures and plant organs is a major challenge for plant biotechnology. Although significant advances have been made in this field through the development of metabolic engineering and synthetic biology techniques, production levels remain insufficient to meet the current market demand for these powerful anticancer drugs. A key stumbling block is the difficulty of genetically transforming the gymnosperm Taxus spp. This review focuses on the progress made in improving taxane production through genetic engineering techniques. These include the overexpression of limiting genes in the taxane biosynthetic pathway and transcription factors involved in its regulation in Taxus spp. cell cultures and transformed roots, as well as the development and optimization of transformation techniques. Attempts to produce taxanes in heterologous organisms such as bacteria and yeasts are also described. Although promising results have been reported, the transfer of the entire PTX metabolic route has not been possible to date, and taxane biosynthesis is still restricted to Taxus cells and some endophytic fungi. The development of a synthetic organism other than Taxus cells capable of biotechnologically producing PTX will probably have to wait until the complete elucidation of its metabolic pathway.